ATTITUDES OF OPEN AND DISTANCE EDUCATION STUDENTS AGAINST IMMIGRANTS (Third Sector Social Economic Review, 2022)
Migration is a challenging process for individuals who migrate, both in terms of maintaining their daily life practices and psychologically. At the same time, the people of the receiving country have difficulties in accepting that immigrants can be permanent due to their effects, adapting and tolerating the socio-cultural changes they have brought. Mutual attitudes are developed due to situations such as mutual distrust, lack of communication and conflicts in terms of both immigrants and local people. Although it is hoped to develop a relationship and positive attitudes that are expected to be based on mutual support and understanding, negative attitudes can also develop due to the problems experienced. This study was carried out to determine the attitudes of Atatürk University Open and Distance Education Faculty students towards immigrants and to determine the differences in their attitudes according to demographic characteristics. For this purpose, the demographic information form developed by the researcher and the Negative Attitudes towards Migrants Scale form developed by Vera et al. (2013) and adapted into Turkish by Günay, Ersoy, Aydıner Boyulu, and Kılıç (2019) were used in the study. As a result of the analysis of the data obtained from 1758 participants who voluntarily participated in the study with the SPSS 20 package program, it was determined that the participants generally had a negative attitude towards immigrants. In addition, it was observed that there was no difference in the attitudes of the participants towards immigrants according to age, education level, employment status and monthly household income. In addition, male participants were found to have more negative attitudes towards immigrants than married participants.
Keywords: Attitudes Towards Immigrants; Open and Distance Education Faculty; Immigration